Penatalaksanaan Fisioterapi Pada Kasus Fasciitis Plantaris Bilaterall di RST. Dr. Soedjono Magelang - Suri, Rizka Putri Amalia Mayang, Arif Pristianto, SSt.FT.,M.Fis (2016)
Background: Fasciitis plantaris is an inflammation of the fascia plantaris. Fasciitis plantaris is an inflammation of the fascia plantaris caused by excessive elongation on fascia plantaris which can result torn then arise an irritation in the fascia plantaris. The factor which causes are age, weight, activity, trauma, the bad use of shoes.Initial symptoms in the emergence of pain in the back of the heel. The pain is getting worst when wake up on the morning and support weight on foot first to the floor. In that case can overcome by modalities psychotherapy. Hence, psychotherapy modalities used in this case ultrasound and exercise that can be lowered the pain. Purpose: To know the psychotherapy in reducing pain, in the case of bilateral fasciitis plantaris using modalities ultrasound and exercise Result: From the therapy obtained by using modalities ultrasound and exercise and education, can help in subtraction pain. Through therapy for 6 times obtained the assessment pain in the heel right pain silence T1: 4.3, being t6: 2,5, pain press t1: 7,2, being t6: 5,3, pain active motion t1: 5, being t6: 2,9, while scores pain in the heel left pain silent t1: 4.3, being t6: 2,2, pain press t1: 6,8, being t6: 5,3, pain active motion t1: 4,7, being t6: 2,9. Conclusion: Ultrasound and exercise can reduce pain on the heel right and heel left in the condition fasciitis plantaris bilateral.